RETRACTED: Teklemariam et al. Isolation and Characterization of a Novel Lytic Phage, vB_PseuP-SA22, and Its Efficacy against Carbapenem-Resistant Pseudomonas aeruginosa. Antibiotics 2023, 12, 497 - Addisu D. Teklemariam; Rashad R. Al-Hindi; Mona G. Alharbi; Ibrahim Alotibi; Sheren A. Azhari; Ishtiaq Qadri; Turki Alamri; Ahmed Esmael; Steve Harakeh (Antibiotics, 2024)
The journal retracts the article, “Isolation and Characterization of a Novel Lytic Phage, vB_PseuP-SA22, and Its Efficacy against Carbapenem-Resistant Pseudomonas aeruginosa”, cited above [...]